Possibilidades da aprendizagem de transformações geométricas com o uso do Cabri-Géomètre - Bilac, Cristina Ulian (2008)
This study is fitted in the Technology of Information and Mathematics Education s line of researching according to the teaching board and the geometric learning, in particular about the Plane Geometry Transformations, and has as a goal to present didactic sequences in which the activities that involve a axial symmetry and the symmetry of rotation promote to the students a development improving in the geometric notions during the process teach-learning of the geometric transformations. For this, we formulated as a research question: in what way the resources of the Cabri-Géomètre software tools promote the learning of the geometric transformations, specially the axial symmetry and the rotation symmetry. For this, it was elaborated an experiment of teaching composed by two stages: the presentation of the software and the exploration of the symmetries using the software Cabri-Géomètre, applied to twenty-three students -Elementary School- 8th grade of a privative school in Santo André city. The stage two was divided into four modulus: Idea of symmetry, reflection, rotation, reflection and rotation. We adopted as a methodology of researching the Design Experiment, aiming the improvement for the didactic sequence elaboration. For the elaboration and analyze of this didactic sequence we supported this research in the Piaget and Garcia Theory (1983) about the development of the geometric notions. The research has as instrument of data collection the recording of the activities resolution in each modulo developed by the students. By the interactions of the students in these activities, the results promote the cogitative interpretations in the different levels of knowledge in the geometric notions: intrafigural, interfigural e transfigural, helped by the resources and tools of the software of dynamical geometric Cabri-Géomètre